The Libri Feudorum (the 'Books of Fiefs') An Annotated English Translation of the Vulgata recension with Latin Text - Stella, Attilio (Brill, 2023)
The Libri Feudorum (the 'books of fiefs') are the earliest written body of feudal customs in Europe, codified in northern Italy c.1100-1250, which gave rise to feudal law as a branch of civil law. Their role in shaping modern ideas of feudalism has aroused an intense debate among medievalists, leading to deep re-thinking of the 'feudal' vocabulary and categories. This book offers an up-to-date English translation with a working Latin text introduced by a historical and historiographical overview of the Libri, thereby providing a valuable tool to understanding the long-standing importance of this collection over nine centuries of European history.